Analisis SWOT Penerapan Digitalisasi untuk Meningkatkan Daya Saing pada Bank Sumut Cabang Syariah Padangsidimpuan - Hamdatun Hakimah; Rosnani Siregar; Nando Farizal (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Digital transformation has encouraged Islamic banks to improve service quality and strengthen competitiveness through technology-based innovation. This study aims to analyze the strengths, weaknesses, opportunities, and threats of digitalization implementation at Bank Sumut Sharia Branch Padangsidimpuan. A qualitative descriptive case study was employed using primary data collected through observations, structured interviews, and documentation involving four employees and fifteen digital banking customers selected through purposive sampling. Data were analyzed through data reduction, data display, conclusion drawing, and SWOT analysis supported by IFAS and EFAS. The findings indicate that digitalization enhances transaction convenience, service efficiency, information transparency, and sharia-based digital services. Key weaknesses include the absence of online account opening, limited digital literacy, and technical system constraints. Opportunities arise from growing smartphone adoption and digital banking acceptance, while cybersecurity risks, digital fraud, and competition remain major threats. This study provides an empirical SWOT-based evaluation of digitalization strategies and offers practical recommendations for strengthening the competitiveness of regional Islamic banks.